Formation of a porous structure in a granulated glass ceramic material from zeolite-bearing rock with alkali additives - Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (2006, 2006)
The possibility of producing foam glass ceramics from zeolite-bearing rocks is investigated. It is established that milling the zeolite-bearing material to a particle size below 0.50 mm and adding 13.8 % alkali ensures at the firing temperature of 850°C the production of a material of bulk density 340 kg/m3, strength 1.6 MPa, and water absorption 13 %. The granulated foam zeolite with the alkali additive is a glass ceramic material of higher strength than foam glass